Shared Book Reading in Early Childhood Education: Effect of Two Approaches on Children's Language Competence, Story Comprehension, and Causal Reasoning. Issue 4 (8th August 2022) - van der Wilt, Femke; Smits-van der Nat, Mireille; van der Veen, Chiel
ABSTRACT: This study investigated the effect of traditional interactive reading and interactive reading using mindmaps on children's language competence and their story comprehension and causal reasoning. Furthermore, we explored teachers' dialogic scaffolding in the two approaches and investigated the relation between teachers' dialogic scaffolding and children's causal reasoning. In total, 7 early childhood teachers and their 176 pupils participated. Classrooms were randomly assigned to the traditional interactive reading group or the interactive reading using mindmaps group. Before and after a six-week intervention, children's language competence was measured using tests for thematic vocabulary, narrative competence, and critical listening. In addition, story comprehension was measured with a short questionnaire and children's causal reasoning and teachers' dialogic scaffolding were assessed by coding videos of shared book reading activities. Outcomes indicated that children significantly improved their language competence over the course of the study, independent of the group to which they were assigned. In addition, findings showed that children's causal reasoning was partly related to teachers' dialogic scaffolding.